tRNAs as a Driving Force of Genome Evolution in Yeast - Guimarães, Ana Rita; Correia, Inês; Sousa, Inês; Oliveira, Carla; Moura, Gabriela; Bezerra, Ana Rita; Santos, Manuel A. S. (Frontiers in Microbiology, 2021)
Transfer RNAs (tRNAs) are widely known for their roles in the decoding of the linear mRNA information into amino acid sequences of proteins. They are also multifunctional platforms in the translation process and have other roles beyond translation including sensing amino acid abundance, interaction with general stress response machinery, and modulating cellular adaptation, survival and death. In this mini-review, we focus on the emerging role of tRNA genes in the organization and modification of the genomic architecture of yeast, and the role of tRNA misexpression and decoding infidelity in genome stability, evolution and adaption. We discuss published work showing how quickly tRNA genes can mutate to meet novel translational demands, how tRNAs speed up genome evolution, and how tRNA genes can be sites of genomic instability. We highlight recent works showing that loss of tRNA decoding fidelity as well as small alterations in tRNA expression have unexpected and profound impacts on genome stability. By dissecting these recent evidence, we hope to lay the groundwork that prompts future investigations on the mechanistic interplay between tRNAs and genome modification that likely triggers genome evolution.